Low-temperature denitration catalyst, preparation method and denitration catalytic filter material
By using a low-temperature denitrification catalyst with a stacked structure of (Mn0.983Fe0.017)2O3 nanosheets, the synergistic effect between Fe and Mn ions is used to solve the problems of low activity and easy poisoning of existing low-temperature denitrification catalysts, and the low temperature is achieved. Effective denitrification and anti-alkali metal poisoning.
Patent Information
- Application Number
- CN202411436887.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-02-18
AI Technical Summary
Existing low-temperature denitrification catalysts have low catalytic activity under low temperature environments and are prone to inactivation due to alkali metal poisoning.
The spherical structure formed by stacking (Mn0.983Fe0.017)2O3 nanosheets is used as a low-temperature denitrification catalyst. Through the synergistic effect between Fe ions and Mn ions, the catalyst is improved, and the catalyst is enhanced by high-temperature calcination preparation method. structural stability.
It significantly improves the activity of low-temperature denitrification catalysts, can reach peaks at lower temperatures, and has good anti-alkali metal poisoning properties, extending the service life of the catalyst.
Smart Images

Figure CN119455968A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of denitration catalysis technology, and in particular to a low-temperature denitration catalyst, a preparation method and a denitration catalytic filter material. Background Art
[0002] NH3-SCR technology is one of the most widely used denitrification technologies. Its principle is that ammonia is used as a reducing agent. Under the action of a catalyst, nitrogen oxides are catalytically reduced to nitrogen and water, which can effectively reduce the emission of nitrogen oxides. Vanadium-tungsten-titanium series catalysts are currently the most commonly used commercial denitrification catalysts, but they still have disadvantages such as V toxicity, narrow operating temperature range, best SCR activity only under 300-400℃, poor low-temperature catalytic activity, and easy alkali metal poisoning.
[0003] In the existing studies on V-free low-temperature denitrification catalysts, metal oxides with variable valence usually show good activity in NH3-SCR, such as MnO x Since Mn has rich and varied valence states and high redox ability, it has become a hot topic in the research of low-temperature denitrification catalysts.
[0004] Although MnO x The catalyst can obtain good activity at low temperature, but there are still problems such as poor structural stability, narrow denitration temperature range, poor water and sulfur resistance. By doping with other metal elements, such as Ce, Sm, Co and other metal elements, not only can the specific surface area of the catalyst be improved and the surface acidity of the catalyst be increased, but also the synergistic effect between different metal elements can be used to enhance the electron transfer effect, which can significantly improve the redox performance of the catalyst and improve the denitration activity of the manganese-based catalyst. Among them, Fe element is used as a modifying element, and the corresponding manganese iron metal oxide denitration catalyst has been proven to have excellent catalytic activity in the SCR reaction.
[0005] However, the catalytic activity is not high in low temperature environments, and it is deactivated by alkali metal poisoning during flue gas treatment. Summary of the invention
[0006] In order to solve at least one of the above technical problems, a denitration catalyst with high low-temperature catalytic activity and not easily deactivated by alkali metal poisoning is developed. The present application provides a low-temperature denitration catalyst, a preparation method and a denitration catalytic filter material.
[0007] On the one hand, the present application provides a low-temperature denitration catalyst, which is (Mn 0.983 Fe 0.017 )2O3 nanosheets stacked to form a spherical structure.
[0008] Optionally, the (Mn 0.983 Fe 0.017)2O3 nanosheets have a diameter of 500nm.
[0009] Optional, (Mn 0.983 Fe 0.017 The spherical particles formed by stacking of 2O3 nanosheets have a size of 1.5 to 2 μm.
[0010] In a second aspect, the present application provides a method for preparing the above-mentioned low-temperature denitration catalyst, comprising the following steps:
[0011] S1, uniformly dispersing the iron salt into the solution containing the MnO2 microspheres to obtain a mixed solution;
[0012] S2, then evaporate the mixed solution to dryness in a water bath, and dry the obtained solid product in an oven,
[0013] S3. The dried product is calcined at high temperature to obtain a low-temperature denitration catalyst.
[0014] Optionally, the iron salt is Fe(NO3)3·9H2O.
[0015] Optionally, the mass fraction ratio of Fe(NO3)3·9H2O / (MnO2+Fe(NO3)3·9H2O) is 20% to 40%.
[0016] Optionally, during the high-temperature calcination, the heating rate is 5°C / min, the calcination temperature is 500°C, and the calcination time is 5h.
[0017] Optionally, the method for preparing the solution containing MnO2 microspheres comprises the following steps:
[0018] A1. Dissolve MnSO4·H2O in water to form a metal salt solution, dissolve NaHCO3 in water to form an alkaline solution, and pour the alkaline solution into the metal salt solution to form a suspension;
[0019] A2, centrifuging, washing and drying the suspension obtained in step A1 to obtain a MnCO3 precipitate;
[0020] A3. The MnCO3 precipitate obtained in step A2 is calcined at high temperature to obtain MnO2 microspheres.
[0021] Optionally, in step A3, the heating rate of the tubular furnace is 5°C / min, the roasting temperature is 400°C, and the roasting time is 5h.
[0022] In a third aspect, the present application provides a denitration catalytic filter material, comprising the above-mentioned low-temperature denitration catalyst.
[0023] In summary, the present invention includes at least one of the following beneficial technical effects:
[0024] 1. Compared with the single MnO2 catalyst, the low-temperature denitrification catalyst of the present application has the advantages of (Mn 0.983 Fe 0.017 )2O3 nanosheets are stacked to form a spherical structure, and the active components are evenly distributed and not easy to agglomerate;
[0025] 2. The synergistic effect between Mn and Fe metal elements can effectively improve the denitrification performance of manganese-based catalysts at low temperatures, and can reach the peak at a lower temperature;
[0026] 3. It has good resistance to alkali metal poisoning and can effectively prevent the catalyst from being poisoned and deactivated; it is doped with transition metal Fe elements, and the raw materials are simple, cheap, and easy to obtain. It does not contain active components of highly toxic substances such as vanadium, and has the advantages of being non-toxic and environmentally friendly;
[0027] 4. The denitrification catalytic filter material prepared in the present application is used for NH3-SCR low-temperature flue gas denitrification, and exhibits excellent NH3-SCR denitrification performance at low temperatures. The denitrification activity is continuously and stably 100% in the temperature range of 175-300°C, and it has excellent resistance to metal poisoning and a longer service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 is the X-ray diffraction (XRD) pattern of the catalyst prepared in Examples 1 to 3;
[0029] Figure 2 is the X-ray diffraction (XRD) pattern of the catalyst prepared in the comparative example;
[0030] Figure 3 (a) is the nitrogen isothermal adsorption-desorption curves of the catalysts prepared in the comparative example and Examples 1 to 3;
[0031] Figure 3 (b) is a pore size distribution diagram of the catalysts prepared in the comparative example and Examples 1 to 3;
[0032] Figure 4 The scanning electron microscope (SEM) images of the catalysts prepared in the comparative example and Examples 1 to 3;
[0033] Figure 5 It is a graph of the denitration test conversion rate of the catalysts prepared in the comparative example and Examples 1 to 3;
[0034] Figure 6 This is the denitrification test conversion rate diagram of the 40%-Fe / MnO2 catalyst prepared in Example 3 and K-40%-Fe / MnO2. DETAILED DESCRIPTION
[0035] This application designs a low-temperature denitration catalyst, which is (Mn 0.983 Fe0.017 )2O3 nanosheets stacked to form a spherical structure.
[0036] The low-temperature denitration catalyst of the present application is prepared by the following method, comprising the following steps:
[0037] S1, uniformly dispersing the iron salt into the solution containing the MnO2 microspheres to obtain a mixed solution;
[0038] S2, then evaporate the mixed solution to dryness in a water bath, and dry the obtained solid product in an oven,
[0039] S3. The dried product is calcined at high temperature to obtain a low-temperature denitration catalyst.
[0040] In the existing studies on V-free low-temperature denitrification catalysts, metal oxides with variable valence usually show good activity in NH3-SCR, such as MnO x Since Mn has rich and varied valence states and high redox ability, it has become a hot topic in the research of low-temperature denitrification catalysts. x The catalyst can obtain good activity at low temperature, but there are still problems such as poor structural stability, narrow denitration temperature range, poor water and sulfur resistance. At present, in the industry, by doping with other metal elements, such as Ce, Sm, Co and other metal elements, not only can the specific surface area of the catalyst be improved and the surface acidity of the catalyst be increased, but also the synergistic effect between different metal elements can be used to enhance the electron transfer effect, which can significantly improve the redox performance of the catalyst and improve the denitration activity of the manganese-based catalyst. Among them, Fe element is used as a modifying element, and the corresponding manganese iron metal oxide denitration catalyst has been proven to have excellent catalytic activity in the SCR reaction.
[0041] Yi Li et al. successfully synthesized a series of MnFeO with different Fe / Mn molar ratios by hydrothermal method. x Nanorods, in the range of 200-350℃, MnFe (0.1) O x showed the highest catalytic performance, NO x The removal rate is close to 100%.
[0042] Inspired by this, the inventors selected Fe, a cheap and easily available raw material, and used MnO2 as a precursor by using a method of impregnation doping followed by high-temperature calcination to prepare MnO2. 0.983 Fe 0.017 )Spherical low-temperature denitrification catalyst formed by stacking 2O3 nanosheets.
[0043] The active components of the catalyst prepared in this application are evenly distributed and not easy to agglomerate. 0.983 Fe0.017 )2O3 low-temperature denitration catalyst has a spinel structure. The unique structural characteristics make the Fe ions and Mn ions have better synergy, which is conducive to the electron transfer and the occurrence of redox reaction. The good dispersibility of the active components of the low-temperature denitration catalyst and the excellent electronic synergy are conducive to the denitration catalytic reaction. In the lower temperature range, that is, within 150℃~300℃, the low-temperature denitration catalyst exhibits excellent low-temperature denitration activity, among which the NO conversion rate can be stably up to 100% within 175℃~300℃.
[0044] At the same time (Mn 0.983 Fe 0.017 )2O3 low-temperature denitrification catalyst has good resistance to alkali metal poisoning. The NO conversion rate can still be stably maintained at more than 90% within 175℃~300℃. It can effectively prevent the catalyst from being deactivated by alkali metal poisoning during flue gas treatment and has broad application prospects in low-temperature NH3-SCR reactions.
[0045] This application is based on the above (Mn 0.983 Fe 0.017 )2O3 low-temperature denitration catalyst, and provides a denitration catalytic filter material including the above-mentioned low-temperature denitration catalyst.
[0046] The present application is further described in detail below with reference to the accompanying drawings and embodiments.
[0047] In the following examples, the main components involved, unless otherwise specified, were purchased from commercially available products.
[0048] Preparation Example
[0049] This preparation example is used to prepare a solution containing MnO2 microspheres.
[0050] Dissolve 21mmol of MnSO4·H2O and 45mmol of NaHCO3 in 200ml of deionized water respectively, then pour the NaHCO3 solution into the MnSO4·H2O solution to form a suspension, and let it stand for 6h;
[0051] (2) centrifuging the precipitate obtained after the suspension was allowed to stand, washing it three times with deionized water and ethanol respectively, and then drying it in an oven at 80° C. for 12 h to obtain a MnCO3 precipitate;
[0052] The MnCO3 precipitate was calcined in a tubular furnace with a heating rate of 5°C / min and a calcination temperature of 400°C for 5 hours to obtain MnO2.
[0053] A certain amount of MnO2 microspheres were ultrasonically dispersed and dissolved in 30 ml of deionized water to obtain a solution containing MnO2 microspheres. Specific embodiments
[0055] Example 1
[0056] This example is used to prepare (Mn 0.983 Fe 0.017 )2O3 low temperature denitrification catalyst.
[0057] Weigh Fe(NO3)3·9H2O and dissolve it in the solution containing MnO2 microspheres prepared in the preparation example, wherein the mass fraction ratio of Fe(NO3)3·9H2O / (MnO2+Fe(NO3)3·9H2O) is 20%. Stir the mixed solution for 2 h using a magnetic stirrer, then evaporate the mixed solution in a 100°C water bath, and dry the final product in an oven at 80°C for 12 h.
[0058] The dried product was properly ground and calcined in a tube furnace at a heating rate of 5°C / min and a calcination temperature of 500°C for 5 h to obtain (Mn 0.983 Fe 0.017 )2O3 low temperature denitration catalyst (20%-Fe / MnO2 denitration catalyst).
[0059] Example 2
[0060] This example is used to prepare (Mn 0.983 Fe 0.017 )2O3 low temperature denitrification catalyst.
[0061] Weigh Fe(NO3)3·9H2O and dissolve it in the solution containing MnO2 microspheres prepared in the preparation example, wherein the mass fraction ratio of Fe(NO3)3·9H2O / (MnO2+Fe(NO3)3·9H2O) is 30%. Stir the mixed solution for 2 h using a magnetic stirrer, then evaporate the mixed solution in a 100°C water bath, and dry the final product in an oven at 80°C for 12 h.
[0062] The dried product was properly ground and calcined in a tube furnace at a heating rate of 5°C / min and a calcination temperature of 500°C for 5 h to obtain (Mn 0.983 Fe 0.017 )2O3 low temperature denitration catalyst (30%-Fe / MnO2 denitration catalyst).
[0063] Example 3
[0064] This example is used to prepare (Mn 0.983 Fe 0.017 )2O3 low temperature denitrification catalyst.
[0065] Weigh Fe(NO3)3·9H2O and dissolve it in the solution containing MnO2 microspheres prepared in the preparation example, wherein the mass fraction ratio of Fe(NO3)3·9H2O / (MnO2+Fe(NO3)3·9H2O) is 40%. Stir the mixed solution for 2 h using a magnetic stirrer, then evaporate the mixed solution in a 100°C water bath, and dry the final product in an oven at 80°C for 12 h.
[0066] The dried product was properly ground and calcined in a tube furnace at a heating rate of 5°C / min and a calcination temperature of 500°C for 5 h to obtain (Mn 0.983 Fe 0.017 )2O3 low temperature denitration catalyst (40%-Fe / MnO2 denitration catalyst).
[0067] The XRD spectra of the catalysts prepared in Examples 1 to 3 are as follows: Figure 1 As shown; nitrogen isothermal adsorption-desorption curve and pore size distribution diagram are shown Figure 3 As shown; scanning electron microscope image as Figure 4 As shown; (Mn prepared in Example 3 0.983 Fe 0.017 )2O3 low temperature denitration catalyst (40%-Fe / MnO2 denitration catalyst) EDS element distribution diagram is as follows Figure 4 shown.
[0068] Comparative Example
[0069] The catalyst used in this comparative example is MnO2; the XRD spectrum is as follows Figure 2 As shown; nitrogen isothermal adsorption-desorption curve and pore size distribution diagram are shown Figure 3 As shown; scanning electron microscope image as Figure 4 shown.
[0070] Table 1 Specific surface area, average pore diameter and total pore volume of catalysts in comparative examples and examples 1 to 3
[0071]
[0072] The denitration activity of the catalysts in Examples 1 to 3 and the comparative example was measured.
[0073] The activity of the catalyst was evaluated using a laboratory quartz tube fixed bed reactor to simulate flue gas conditions. The specific test steps are as follows:
[0074] (1) Catalyst loading: Weigh 0.2 g of the catalyst obtained after grinding and load it into a quartz tube fixed bed reactor;
[0075] (2) Introduction of simulated flue gas: The simulated flue gas composition is: 500 ppm NO, 500 ppm NH3, 3% O2, and Ar as the balance gas.
[0076] (3) Record NO concentration: Turn on the heating furnace and raise the temperature from 100°C to 300°C at a rate of 2°C / min. The reaction is carried out at different temperatures. The denitrification catalytic performance data that changes with temperature is recorded after being kept stable for 30 minutes at each temperature point. The concentration data is collected through the NO flue gas analyzer;
[0077] (4) End: Turn off the heating furnace, first turn off NO and NH3, then turn off O2 and Ar.
[0078] (5) Calculation of catalyst activity: The NO conversion rate is used to evaluate the catalyst activity. The calculation formula is as follows:
[0079] NO conversion rate = ([NO]in - [NO]out) / [NO]in * 100%, wherein [NO]in represents the NO concentration in ppm at the inlet of the fixed bed reactor, and [NOx]out represents the NO concentration at the outlet of the fixed bed reactor.
[0080] The test results are as follows Figure 5 As shown in the figure, it can be seen that the (Mn 0.983 Fe 0.017 The denitration activity of the 2O3 low-temperature denitration catalyst is much higher than that of the MnO2 catalyst. It can be seen that the catalytic activity of the catalyst of the present application increases rapidly with the increase of temperature after 100°C, and can reach a peak at about 175°C, while the catalyst in the comparative example can only reach a peak at 200°C, and the denitration activity gradually decreases after 225°C. Figure 5 It can be seen that among the examples of the present application, the 40%-Fe / MnO2 catalyst prepared in Example 3 exhibits the best denitrification activity.
[0081] For the (Mn 0.983 Fe 0.017 )2O3 low temperature denitration catalyst (40%-Fe / MnO2 denitration catalyst) was subjected to alkali metal poisoning simulation experiment. K was selected to study the catalyst's ability to resist alkali poisoning.
[0082] The K-poisoned catalyst was prepared by impregnation with KNO3 solution, and the K loading was set to 0.2 mmol K / g 40%-Fe / MnO2.
[0083] Weigh 0.0182g KNO3 and add it to a beaker containing 20ml deionized water. Stir it with a magnetic stirrer for 20min to obtain a KNO3 solution. Then add 0.9g 40%-Fe / MnO2 catalyst and stir for 2h to mix the solution evenly. Finally, dry it in a 100℃ water bath and dry the product in an oven at 80℃ for 12h.
[0084] The dried product was ground appropriately and calcined in a tubular furnace at a heating rate of 5°C / min and a calcination temperature of 300°C for 5 hours to obtain a K-40%-Fe / MnO2 catalyst.
[0085] The 40%-Fe / MnO2 catalyst and K-40%-Fe / MnO2 catalyst were tested for denitration. The test results are as follows: Figure 6 As shown. Figure 6 It can be seen that (Mn 0.983 Fe 0.017 )2O3 low-temperature denitration catalyst (40%-Fe / MnO2 denitration catalyst) has good resistance to alkali metal poisoning. The NO conversion rate can still be stably maintained at more than 90% within 175℃-300℃, which can effectively prevent the catalyst from being poisoned and deactivated.
[0086] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A low-temperature denitration catalyst, characterized in that: Mn 0.983 Fe 0.017 )2O3 nanosheets stacked to form a spherical structure.
2. The low-temperature denitration catalyst according to claim 1, characterized in that: The (Mn 0.983 Fe 0.017 )2O3 nanosheets have a diameter of 500nm.
3. The low-temperature denitration catalyst according to claim 1, characterized in that: (Mn 0.983 Fe 0.017 The spherical particles formed by stacking 2O3 nanosheets have a size of 1.5-2 μm.
4. A method for preparing a low-temperature denitration catalyst according to claim 1, characterized in that: The following steps are involved: S1, uniformly dispersing the iron salt into the solution containing the MnO2 microspheres to obtain a mixed solution; S2, then evaporate the mixed solution to dryness in a water bath, and dry the obtained solid product in an oven, S3. The dried product is calcined at high temperature to obtain a low-temperature denitration catalyst.
5. The preparation method according to claim 4, characterized in that: The iron salt is Fe(NO3)3·9H2O.
6. The preparation method according to claim 5, characterized in that: The mass fraction ratio of Fe(NO3)3·9H2O / (MnO2+Fe(NO3)3·9H2O) is 20% to 40%.
7. The preparation method according to claim 4, characterized in that: During the high temperature calcination, the heating rate is 5°C / min, the calcination temperature is 500°C, and the calcination time is 5h.
8. The preparation method according to claim 4, characterized in that: The method for preparing the solution containing MnO2 microspheres comprises the following steps: A1. Dissolve MnSO4·H2O in water to form a metal salt solution, dissolve NaHCO3 in water to form an alkaline solution, and pour the alkaline solution into the metal salt solution to form a suspension; A2, centrifuging, washing and drying the suspension obtained in step A1 to obtain a MnCO3 precipitate; A3. The MnCO3 precipitate obtained in step A2 is calcined at high temperature to obtain MnO2 microspheres.
9. The preparation method according to claim 8, characterized in that: In step A3, the heating rate of the tubular furnace is 5°C / min, the calcination temperature is 400°C, and the calcination time is 5h.
10. A denitration catalytic filter material, characterized in that: It comprises the low-temperature denitration catalyst as claimed in claim 1.